A feminist approach to eating disorders in China: a qualitative study - Su Holmes; Hua Ma (Journal of Eating Disorders, 2023)
Abstract Background As women continue to be more at risk from eating disorders, gender has often been a focus of concern in transcultural research. Yet feminist, qualitative studies which prioritize the voices of women/girls remain rare within transcultural work suggesting the need for greater interaction between these fields. This article seeks to contribute to the exploration of the applicability of feminist paradigmslargely developed in the West—to experiences of EDs in non-western contexts. Methods This article draws on semi-structured interviews with 12 women from urban China with self-reported experience of Bulimia Nervosa (BN) and binge eating disorder (BED) in order to explore the complex ways in which gender may be implicated within eating/body distress from a transcultural point of view. The data is analysed through Reflexive Thematic Analysis. Results The data analysis suggested two broad themes: (1) Chinese versus Western codes for judging female appearance: from surveillance to liberation (2) Discipline, appetite and control: the gendered/cultural meanings of binging and purging. In terms of the first theme, many participants had spent time in the West which was understood as a less regulated context in terms of gendered body surveillance and eating. Complicating existing assumptions about the ‘Westernisation’ thesis, different communication codes and peer interactions across Chinese and Western contexts played a central role in how participants experienced their bodies. In the second theme, binging and purging emerged as a way to manage a number of contradictions surrounding Chinese femininity, including respecting familial food cultures, contradictory discourses on female ‘appetite’, and the need to display a female body which signified cultural imperatives of self-restraint and discipline. Conclusions The data emphasises the importance of examining the culturally specific meanings of eating problems and their gendered contexts, whilst there is clearly much that echoes Western feminist work on Western samples. Although limited, the study crucially points to the importance of examining how ED subcategories other than AN can be explored from a transcultural and feminist point of view.